Analisis Pengaruh Desain, Kualitas, dan Harga Terhadap Tingkat Kepuasan Para Pelaku UMKM di Rumah Kemasan Humbang Hasundutan Menggunakan Metode Analisis Regresi Linear Berganda - Kristine Lumban Gaol; Joumil Aidil Saifuddin Z. S (Jurnal Serambi Engineering, 2025)
MSMEs play a major role in Indonesia's economy, both as job providers and as key drivers of economic growth. However, MSME players often face challenges in maintaining competitiveness in an increasingly competitive market. This study aims to analyze the influence of design, quality, and price on the level of satisfaction of MSME players at the Humbang Hasundutan Packaging House. This Packaging House was established to improve the quality of local product packaging to make it more attractive and competitive. The research method uses a multiple linear regression analysis approach with primary data obtained from questionnaires filled out by local MSME players. The results showed that design and price have a significant influence on the level of satisfaction of small and medium enterprises (MSMEs), with design being the most dominant. An attractive design can increase product attractiveness and strengthen brand identity. Prices that match product quality are also proven to be able to provide more value for customers. However, product quality partially does not have a significant effect on satisfaction levels, which may be due to differences in customer perceptions or expectations. The coefficient of determination of 59.4% indicates that the design, quality and price variables are good enough to explain variations in the level of satisfaction of MSMEs, while the rest is influenced by other factors that have not been studied. Based on these results, it is recommended that future research explore other variables, such as service or innovation, which may contribute to MSME satisfaction more comprehensively.